Capitalist globalization: mechanisms of economic and political regulation (2012)
This article makes a theoretical analysis on the mechanisms that influence governments elections, likewise the collective action in decentralized networks as ways from which citizens can regulate the political decisions and, through these, also regulate economic decisions within the framework of capitalist globalization. Mechanisms on the first track are analyzed based on theory principal-agent, and on the second one, from the theory of social networks. In both cases, the difficulty lies in the effective implementation of the devices for the achievement of the proposed objectives. On these mechanisms, it is possible to identify some conditions to bring effectiveness and power to citizen political action, which are related to the new sociopolitical dynamics.